Is the Horn of Africa’s ‘Cold War’ over? Abiy Ahmed’s early reforms and the rapprochement between Ethiopia and Eritrea - Ylönen, A. (African Security Review, 2019)
On 9 July 2018, Ethiopia and Eritrea signed a historical agreement pledging to end their mutual animosity and work for peace. The unprecedented rapprochement was facilitated by the new leadership in Ethiopia, merging interests between the two states and external mediation. This commentary looks into Ethiopian Prime Minister Abiy Ahmed Ali’s early reform initiatives and the dynamics of the rapprochement between Ethiopia and Eritrea.